Analisis Sosiodemografi, Status Kek, Dan Imt Ibu Menyusui Dengan Status Gizi Bayi Usia 0-12 Bulan Di Puskesmas Oesapa - Mindarsih, Theresia; Esem, Odilia (Jurnal Maternitas Kebidanan, 2024)
The results of research on the nutritional status of children under two years of age in Indonesia in 2020 were that 1.3% were very underweight and 5.4% were underweight. There was an increase in 2021 which stated that 7.0% of the population under two years old experienced wasting. At the Oesapa Community Health Center, the number of toddlers experiencing nutritional status problems in 2022 in Oesapa will be 64.1%. This shows that nutritional problems are still high. The aim is to analyze the relationship between age, education, income, MUA and BMI of breastfeeding mothers with the nutritional status of babies. This research used a quantitative design with a cross sectional approach and was tested analytically. The research population was 125 mothers who were still breastfeeding babies aged 0-12 years, a sample of 98 respondents. The instruments in this research were questionnaires, observation sheets and scales, Lila tape.. The sampling technique was purposive sampling. The results of statistical tests show that there is no relationship with age (0.395) education (0.769). There is a relationship between family income (0.003), MUA (0.001) and BMI (0.046) with the baby's nutritional status. The conclusion is that there is no relationship between age and education and the nutritional status of babies. There is a relationship between family income, KEK status, BMI and the nutritional status of babies 0-12 months.